Amatørarkæologer i Danmark - Andresen, Jane Kjærgaard (Kuml, 2001)
Amateur archaeologists in Denmark The article briefly sums up the history of amateur archaeology in Denmark and mentions the most renowned amateur archaeologists and collectors of artefacts, mainly from the island Fyn. Attention focuses on describing the close collaboration between amateur and profession al archaeologists, which has resulted in the institution of museums all over the country, often through donations of extensive artefact collections from skilful and wealthy amateur archaeologists. The first museum was established in Copenhagen by Ole Worm (1588-1654), who studied the Danish prehistory. The king, Frederik III (1609-1670), made the museum into a kunstkammer, which included not only archaeological artefacts but also curiosities. Later, the artefact collections were gathered in the Old Nordic Museum, which became the present National Museum in 1892. Ole Worm’s contemporary, the nobleman Jesper Friis (1593-1643) of Ørbæklunde on Fyn created an extensive and comprehensive kunstkammer including two Egyptian mummy coffins (fig. 1). Another native of Fyn, Professor Thomas Broder Bircherod (1661-1731) also had a collection of curios. In the 19th century, Lauritz Schebye Vedel Simonsen (1780-1858), the owner of the manor Elvedgård, and Niels Frederik Bernhard Sehested (1813-1882), owner of the manor Broholm, had large collections of artefacts. The latter was a talented amateur archaeologist, who undertook systematic excavations of almost 400 Iron Age graves on the Møllegårdsmarken site. The finds were published in well-illustrated books. Sehested had a small museum built in the manor garden, where he exhibited his finds. The museum still exists (fig. 2). He also experimented with the practical manufacturing and use of prehistoric tools – a novelty at the time (fig. 3). Even King Frederik VII (1808-1863), once the governor of Fyn, was a passionate collector, who undertook or initiated many excavations. The 20th century saw many wealthy amateur archaeologists, who built museums and issued archaeological publications, as for instance the prefect of the island Bornholm, Emil Vedel (1824-1909), who – assisted by the teacher, Johan Andreas Jørgensen (1840-1908) – made comprehensive investigations into several hundred graves at Lousgaard on Bornholm. Vedel initiated the horizontalstratigraphic excavation method, which resulted in the introduction of the Pre-Roman Iron Age in Danish archaeology. As an acknowledgement for this, Emil Vedel was appointed vice president of ”Det kongelige Nordiske Oldskriftselskab,” a credit to an amateur archaeologist! The chemists Christen Mikkelsen (1844-1924) and his son, Poul Helweg Mikkelsen (1876-1940) represented two generation s of very active amateur archaeologists on Fyn. Both left large private collections, which they willed to The National Museum and Fyns Stiftsmuseum (the museum of the diocese of Fyn) (fig. 4). Poul Helweg Mikkelsen is especially remembered for his excavation of the Ladby Viking ship. Out of his own pocket he paid for the building of a cupola covering the Viking ship, which was left in situ, thus making this Viking ship grave unique in Scandinavia. JensWinther (1863-1955), a grocer on the island of Langeland, paid a museum with his own money (fig. 5). He was a skilful amateur archaeologist, who carried out numerous excavations and introduced a new excavation technique, surface digging, involving the gradual exposure of the surface through the removal of thin successive earth layers – a technique that set a fashion. His excavations at the Troldebjerg site functioned as training excavations for future professional archaeologists. For instance, P.V. Glob, the later professor of archaeology and keeper of national antiquities, was one of Winther’s ”pupils”. Also Winther’s lifelong housekeeper, Miss Hornum, was a skilful amateur archaeologist – so skilful that she was invited to take part in the excavation of Inuit settlements in Greenland. Later she was admitted the second female member of ”Det kongelige Nordiske Oldskriftselskab,” following professor Brøndsted’s recommendation. Svend Dyhre Rasmussen (fig. 6), an amateur archaeologist from Sjælland, found the famous medieval high-backed fields and the adjoining village of Borup Ris. His fellow islander, Karl Kristian Nielsen (fig. 7) was a hardworking amateur archaeologist, who undertook both prehistoric and medieval excavations for forty years. He was a modest, self-taught man working as a charcoal burner and thus nicknamed ” the learned charcoal burner”. He was the first amateur archaeologist honoured with the membership of ”Det kongelige Nordiske Oldskriftselskab” (fig. 8). The article also mentions the wide section of the population – comprising all classes – that has contributed to collectin g and preserving our relics of the past in such a comprehensive manner. Another purpose of the article is to show the connection between important events in Danish history and the amateur archaeological initiatives that resulted from them. The article gives a survey of Danish amateur archaeology, which is organised in numerous associations that stimulate the public interest in this field. A new initiative was the founding of a countrywide organisation of amateur movements, the SDA, in 1990 (fig. 9).The SDA has initiated courses, publication of an amateur archaeological periodical and the ambitious project, ”Operation Golden Horn” aiming at a countrywide registration and mapping of finds and relics. The history of the amateur archaeologist associations on Fyn is described, including examples of the work of smaller groups (fig. 11). The cooperation between amateur archaeologists and museum employees on Fyn culminated in 1984 with the exhibition” Past time and spare time”. An important part of amateur archaeologists’ work is the participation in the annual excavation camps, where the amateurs enjoy the pleasure of finding artefacts and learn how to register them scholarly correctly. Cooperation on a Scandinavian level resulted in a Nordic Amateur Archaeologists’ Excavation Camp (the NAU) in connection with Odense’s 1000th anniversary in 1988 (fig. 12). Since then, similar excavation camps have been held in other Nordic countries, and in Estonia. The cooperation with Estonia has given a wider perspective, which includes international cooperation at different levels. The amateur archaeologists’ knowledge of their own neighbourhood has proved important, as they co nt act the profession al archaeologists when farming methods or public construction work is unexpectedly revealing archaeological finds. In such cases, retired and unemployed amateur archaeologists have made an ”ambulance service”, which offers assistance to museums at short notice. Another special initiative was taken by the amateur ar chaeologists on Bornholm, who created a special branch for detector amateurs. This has helped both Norwegian and Swedish museums investigating known sites and thus gain a more differentiated picture of Iron Age settlements. A third special branch of amateur work is the investigation of the submarine settlement of Tybrind Vig, which is an example of a well functioning coopertion with the marine-archaeological group in Fredericia. When in the 1991, Professor Henrik Thrane, Doctor of Philosophy, made the Hollufgård Museum on Fyn and its collection s more user-friendly and accessible to the public by creating ”open stores”, he also gave the amateur archaeologists the possibility of self-tuition. The publication of the archaeological journal ”Archaeology and the natives of Fyn” in 1979 was a result of cooperation between the museum and amateurs (fig. 13). Finally, in 1993, the SDA journal now carrying the name of” Archaeology for everyone” was published. To stimulate the interest in archaeology among the youth, so-called Hugin and Munin clubs have been started, with branches in Copenhagen, on Fyn and in Jutland. The Erik Westerby foundation (initiated by this famous amateur archaeologist) was created to support Danish archaeologists. In 1994, Axel Degn Johansson was the first amateur archaeologist to receive the price, along with 100.000 Dkr, and later another twelve amateur archaeologists have enjoyed grants and presents of money from the foundation. Finally, the importance of the amateur movement for the present and the future is mentioned, and it is stressed that good cooperation between amateurs and museum professionals is very important. Amateur archaeologists will also benefit from the new and refined methods of dating and analysing archaeological finds and – when detecting new finds in the field – of the exact position determination offered by the GPS system. The importance of publicattention on archaeology is stressed, and so the interest of amateur archaeologists is seen as a necessary part in the important and comprehensive task of preserving the past for the future. Jane Kjærgaard Andresen Odense Translated by Annette Lerche Trolle